Erratum: RONGQIAN BI, HUA QU, LING LI, CHANGLIN ZHAO & ZAI-WEI GE (2025) Inocybe caryicola (Inocybaceae, Agaricales), a new species from Yunnan, China. Phytotaxa 718 (2): 96–108. - Bi, Rongqian; Qu, Hua; Li, Ling; Zhao, Changlin; Ge, Zai-Wei (Phytotaxa, 2026)
N/A